2012
DOI: 10.1007/s00330-012-2393-6
|View full text |Cite
|
Sign up to set email alerts
|

Emphysema lung lobe volume reduction: effects on the ipsilateral and contralateral lobes

Abstract: Computed tomography allows assessment of the treatment of emphysema with endobronchial valves. • Endobronchial valves can reduce the volume of an emphysematous lung lobe. • Compensatory expansion is greater in ipsilateral lobes than in the contralateral lung. • Reduced air trapping is measurable by RV/TLC and smaller low attenuation area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 35 publications
3
38
0
1
Order By: Relevance
“…4 6). The coefficients of repeatability and reproducibility of emphysema scores also decreased when using semi-automated segmentation and had ranges that varied depending on the target lobe and selected threshold of emphysema.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 6). The coefficients of repeatability and reproducibility of emphysema scores also decreased when using semi-automated segmentation and had ranges that varied depending on the target lobe and selected threshold of emphysema.…”
Section: Resultsmentioning
confidence: 99%
“…When emphysema affects more than 50% of the volume of one lobe and relatively spares adjacent ipsilateral lobes, the patient can benefit from bronchoscopic lung volume reduction (3). CT quantifies the severity and distribution of the disease and monitors the effects of treatment (3,4). However, the intrinsic variability of CT measures of lobar volumes and emphysema scores can potentially influence the therapeutic management of these patients (5).…”
Section: Discussionmentioning
confidence: 99%
“…These thresholds were chosen on the basis of cluster analysis and are consistent with recent reports [21]. Group differences according to continuous data were evaluated using two-sample t-tests for one variable, and the generalised linear model for multivariate analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The upper part of regional perfusion is similar to the upper lobe of the lung, and the lower part is similar to that of the lower lobe (50). A series of studies found that BLVR would cause a decrease in target lung perfusion and increase ipsilateral non-target lobe and contralateral lung perfusion (51)(52)(53). Therefore, assessment of lobe perfusion before treatment may be an index of the success of EBV.…”
Section: Other Predictorsmentioning
confidence: 99%